Theoretical Study of C2H5 + NCO Reaction: Mechanism and Kinetics - Nan-Nan Wu; Shun-li OuYang; Liang Li (Journal of Chemistry, 2018)
Theoretical investigations are performed on mechanism and kinetics of the reactions of ethyl radical C2H5 with NCO radical. The electronic structure information of the PES is obtained at the B3LYP/6-311++G(d,p) level of theory, and the single-point energies are refined by the CCSD(T)/6-311+G(3df,2p) level of theory. The rate constants for various product channels of the reaction in the temperature range of 200–2000 K are predicted by performing VTST and RRKM calculations. The calculated results show that both the N and O atoms of the NCO radical can attack the C atom of C2H5 via a barrierless addition mechanism to form two energy-rich intermediates IM1 C2H5NCO (89.1 kcal/mol) and IM2 C2H5OCN (64.7 kcal/mol) on the singlet PES. Then they both dissociate to produce bimolecular products P1 C2H4 + HOCN and P2 C2H4 + HNCO. At high temperatures or low pressures, the reaction channel leading to bimolecular product P2 is dominant and the channel leading to P1 is the secondary, while, at low temperatures and high pressures, the collisional stabilization of the intermediate plays an important role and as a result IM2 becomes the primary product. The present results will enrich our understanding of the chemistry of the NCO radical in combustion processes.